Effect of vacuum-packing method on the shelf -life of Capoeta umbla sausages - Özpolat, E.; Patir, B.; Guran, H.S.; Gul, M.R. (Iranian Fisheries Research Organization, 2014)
The effect of vacuum packing on the shelf-life of sausages produced from Capoeta umbla were investigated during storage periods. For this purpose, microbial, chemical and sensory changes were analyzed throughout the storage time. The microbial flora of the sausages comprised mainly mesophilic bacteria, psychrotrophic bacteria, lactic acid bacteria, yeast and molds. Escherichia coli, Staphylcoccus aureus and coliforms were not detected in the sausage samples. Total volatile basic nitrogen (TVB-N) and thiobarbituric acid (TBA) increased gradually with storage time while the concentration of moisture was not affected during the storage period. Application of vacuum-packing at 4±1°C extended the shelf-life of sausage samples by approximately 30 days.
Keywords: Capoeta umbla; Fish sausage; Shelf-life; Vacuum packed